Initiatives to Improve Quality of Education in the Kurdistan Region-Iraq Administration, School Monitoring, Private School Policies, and Teacher Training - Vernez, Georges (RAND Corporation, 2016)
RAND supported the Kurdistan Regional Government in its aims to restructure its Ministry of Education, develop a plan for a school quality assurance system, review effectiveness of monitoring and support of private schools, and assess the quality of in-service teacher training. RAND researchers conducted interviews, reviewed literature, examined case studies in other countries, provided analysis, and developed implementation guidelines.